GREEN MARKETING STRATEGIES AND PERCEIVED VALUE TO PURCHASE DECISIONS FROM AN ISLAMIC BUSINESS PERSPECTIVE: A Study of Sakara Coffee Consumers in Bandar Lampung - Nahdatul Karimah; Muhammad Iqbal Fasa; Nurhayati Nurhayati (Ad Deenar: Jurnal Ekonomi dan Bisnis Islam, 2026)
Increasing consumer awareness of environmental issues is driving perpetrator Coffee shop businesses implement green marketing strategies as part of their business. from sustainable marketing. From an Islamic business perspective, marketing is not only profit oriented, but also value oriented. ethics, social responsibility, and environmental conservation. This research aims This study analyzes the influence of green marketing strategies and perceived value on consumer purchase decisions from an Islamic business perspective at Sakara Coffee in Bandar Lampung. The study uses a multidisciplinary approach. quantitative descriptive-causal with primary data from 99 respondents selected through purposive sampling. Structural Equation Modeling Partial Least Square (SEM-PLS) with SmartPLS 4 was used for the analysis. The study's findings demonstrate that purchasing decisions are positively and significantly impacted by perceived value and green marketing tactics. and concurrently. This finding confirms that the implementation of green marketing is in harmony with Islamic business principles and is able to increase perceived value by consumers can encourage decision ethical and sustainable purchasing.